PENGARUH PARTISIPASI ANGGARAN TERHADAP BUDGETARY SLACK DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI - Usmar Musawir; Muttiarni Muttiarni (Magister Akuntansi, Universitas Atma Jaya Makassar, 2019)
This Riset is purposed for knowing the influence of budgeting participation to budgetary slack using organization commitment as moderation variable. This riset using quantitative method. The population of 90 employees, for a sample of 40 people. Data analytical method which used is moderated regression analysis. Depend on the result of the data analytic be concluded that there are 3 results: 1) Budgeting participation can’t influence the budgetary slack, 2) Organization commitment have positive influence to the budgetary slack, 3) Budgeting participation and organization commitment have positive influence and significant to the budgetary slack.